К расчету червячной фрезы для нарезения червячных колес цилиндрических червячных передач с круговинтовым профилем червяка - Макаров, А. М. (НТУ "ХПИ", 2005)
Розглядується геометрiя черв'ячної фрези для нарiзування черв'ячного колеса з круговинтовим профiлем черв'яка.

The subject under study is the geometry of warm-gear cutter to thread the worm-wheel with the circular-screw warm profile.
Keywords: осевое сечение; линии касания; режущая кромка; ряд Маклорена